The Effect of Population and Human Development Index on Economic Growth Pematangsiantar City - Darwin Damanik; Elidawaty Purba; Arnold Sultantio Hutabarat (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the effect of population and human development index on economic growth in Pematangsiantar City, both partially and simultaneously. The type of data used is secondary time series data with a time period of 2004 – 2019. The data analysis technique uses multiple regression analysis with ordinary least squares (OLS). The results showed that partially the population had a significant effect on the economic growth of Pematangsiantar City. The Human Development Index (HDI) has no significant effect on the economic growth of Pematangsiantar City. Meanwhile, simultaneously, the population and the human development index have a significant effect on the economic growth of Pematangsiantar City.